Predominant contribution of cis-regulatory divergence in the evolution of mouse alternative splicing - Gao, Qingsong (Mol Syst Biol, 2015)
Divergence of alternative splicing represents one of the major driving forces to shape phenotypic diversity during evolution. However, the extent to which these divergences could be explained by the evolving cis-regulatory versus trans-acting factors remains unresolved. To globally investigate the relative contributions of the two factors for the first time in mammals, we measured splicing difference between C57BL/6J and SPRET/EiJ mouse strains and allele-specific splicing pattern in their F1 hybrid. Out of 11,818 alternative splicing events expressed in the cultured fibroblast cells, we identified 796 with significant difference between the parental strains. After integrating allele-specific data from F1 hybrid, we demonstrated that these events could be predominately attributed to cis-regulatory variants, including those residing at and beyond canonical splicing sites. Contrary to previous observations in Drosophila, such predominant contribution was consistently observed across different types of alternative splicing. Further analysis of liver tissues from the same mouse strains and reanalysis of published datasets on other strains showed similar trends, implying in general the predominant contribution of cis-regulatory changes in the evolution of mouse alternative splicing.